Regenerative Strategies for the Treatment of Knee Joint Disabilities - Oliveira, Joaquim Miguel; Reis, Rui Luís.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents regenerative strategies for the treatment of knee joint disabilities. The book is composed of four main sections totaling 19 chapters which review the current knowledge on the clinical management and preclinical regenerative strategies. It examines the role of different natural-based biomaterials as scaffolds and implants for addressing different tissue lesions in the knee joint. Section one provides an updated and comprehensive discussion on articular cartilage tissue regeneration. Section two focuses on the important contributions for bone and osteochondral tissue engineering. Section three overview the recent advances on meniscus repair/regeneration strategies. Finally, section four further discusses the current strategies for treatment of ligament lesions. Each chapter is prepared by world know expert on their fields, so we do firmly believe that the proposed book will be a reference in the area of biomaterials for regenerative medicine.
Section I: Articular Cartilage Lesions: Clinical Management and Regenerative Strategies -- Chapter 1: Knee Articular Cartilage -- Chapter 2: Clinical Management of Articular Cartilage Lesions -- Chapter 3: Synovial Knee Joint : Viscosupplementation -- Chapter 4: Ostearthritis Management -- Chapter 5: Advances in Biomaterials for the Repair of Articular Cartilage Defects -- Chapter 6: Cartilage Tissue Engineering and Regenerative Strategies -- Section II: Osteochondral Lesions of the Knee: From Repair towards Regeneration -- Chapter 7: Fundamentals on Osteochondral Tissue Engineering -- Chapter 8: Pre-clinical and Clinical Management of Osteochondral Lesions -- Chapter 9: Rapid Prototyping in Osteochondral Tissue Engineering -- Chapter 10: Biomimetic Approaches for the Engineering of Osteochondral Tissues -- Chapter 11: Osteochondral Tissue Engineering and Regenerative Strategies -- Section III: Meniscus Injuries: Replacement, Repair and Regeneration -- Chapter 12: Basics on Meniscus.-Chapter 13: Biomaterials for Meniscus Repair -- Chapter 14: Advanced Regenerative Strategies -- Section IV: Knee Ligament Injuries -- Chapter 15: Fundamentals on Knee Ligaments and Injuries -- Chapter 16: Clinical Management of Ligament Injuries and Postoperative Rehabilitation -- Chapter 17: Biomaterials as Tendon Substitutes: Current Developments -- Chapter 18: Ligament Tissue Engineering -- Chapter 19: Ligament lesions: Regenerative Strategies and Future Trends.
Keywords: Biomedical engineering; Biomaterials; Regenerative medicine; Mechanics, Applied; Solids; Biomedical Engineering and Bioengineering; Biomaterials; Regenerative Medicine and Tissue Engineering; Solid Mechanics